Subtype-Selective Dopamine Receptor Radioligands for PET Imaging: Current Status and Recent Developments - Banerjee, A.; Prante, O. (Current Medicinal Chemistry, 2012)
This review presents a general overview of the subtype-selective dopamine receptor radioligands for in vivo imaging of dopamine receptor expression by positron emission tomography (PET). Besides the 11C- and 18F-labeled radioligands which are already in clinical use, a summary of subtype-selective radioligands which had been studied in vitro and in vivo is provided, which shines light onto the current status and recent developments in this field of radiopharmaceutical research.
Keywords: PET